Technogenic Magnetic Particles in Soils and Ecological–Geochemical Assessment of the Soil Cover of an Industrial City in the Ural, Russia - Andrei Vasiliev; Svetlana Gorokhova; Mikhail Razinsky (Geosciences, 2020)
The work is devoted to the study of pollution by technogenic magnetic particles and heavy metals of soils in the city of Gubakha, Middle Ural (Russia). The aim of the work is the ecological and geochemical assessment of the elemental chemical composition of the soils of the city of Gubakha, and the establishment of the geochemical role of technogenic magnetic particles (TMPs). For the first time, the regularities of the spatial distribution of magnetic susceptibility in the soils of the city of Gubakha were revealed, and the morphology, elemental and mineralogical compositions of magnetic particles in the soils of an industrial city in the Middle Urals were characterized using the methods of the chemical extraction of iron compounds, magnetic separation, ESEM/EDS, and Mössbauer spectroscopy. The magnetic phase of soils contains magnetite/maghemite, hematite, pyrrhotite, intermetallic alloys and chromite. Spherical magnetic particles are hollow, and have a magnetite shell and a varied surface texture. The crystal lattice of magnetite is characterized by low stoichiometry. The heavy metals Zn, Cu, Ni and Cr are concentrated in magnetic particles and have a high correlation coefficient with magnetic susceptibility. The level of contamination of Cu, Ni, Zn, Cr and Mn in the soils of a residential zone of Gubakha, estimated by the value of the pollution load index (PLI), was high. The Igeo index for Fe ranges from 6.2 to 12.2, for Cu–1.1 and Ni–1.1. The combination of methods for measuring magnetic susceptibility, determining the mineralogical composition of iron compounds, and determining the elemental chemical composition by X-ray fluorescence, has shown the effectiveness of an integrated approach for carrying out an ecological–geochemical assessment of the soil cover of Gubakha.